Metacognitive Habits: Contradiction in Terms or Valid Theoretical Concept? The Role of Metacognition in Habitual Behavior. Issue 3 (4th May 2017) - Kovač, Velibor Bobo
ABSTRACT: The aim of the present article is to present data showing that habitual actions might be conceptualized as metacognitive habits. The study is based on 3 data collections assessing smoking and school attendance. Habits were measured by a self-report habit index (SRHI) scale that assesses the level in which given behaviors are performed without self-awareness. Metacognitions were measured by the Mental Constructions (MCs) scale that assesses the level of awareness in performing behaviors in question. The results show that MCs and SRHI have (a) moderate to strong positive correlations and (b) similar relations to dependent variables. The study concludes that the further explorations of metacognitive habits are warranted.